MONTE CARLO CALCULATION OF THERMAL AND EPITHERMAL NEUTRON SELF-SHIELDING FACTORS - VUONG , HUU TAN; PHAM , NGOC SON; PHU , CHI HOA; BACH , NHU NGUYEN (Nuclear Science and Technology, 2011)
Neutron activation measurement is often performed in a reactor based neutron spectrum. When the size of the irradiation sample is not small enough and resonance peaks present in the cross section of the sample nuclide, the thermal and resonance self-shielding effects of neutron flux distribution in the sample must be considered for correction. In this work, the Monte Carlo code MCNP-5 has been applied for calculation of the self-shielding factors for several standard samples and neutron monitors that are often used in measurements of thermal neutron capture cross sections and resonance integrals. The results of calculation are tabulated with different sample thickness and different irradiation geometries.